(untitled) (Research, Society and Development, 2025)
In order for the knowledge and culture of quilombola communities to be preserved, it is necessary to know what the socioeconomic conditions of these communities are like. To do this, it is necessary to understand whether there is basic infrastructure so that people can remain in their communities. Are the conditions in which they live together with State actions and/or initiatives capable of making the ways of life in quilombola communities viable? Do they meet their social needs and promote social equity and equal rights? The work aims to characterize the socioeconomic profile of family farmers in the Malhadinha Community, which belongs to the municipality of Brejinho de Nazaré – TO. 50 questionnaires were administered in the community, directly approaching residents, with the authorization of the community leader. In the Malhadinha community, most families live on an average income of one minimum wage and most of the people interviewed work as rural workers, agriculture is the predominant economic activity. The community has basic education infrastructure for the initial years. Basic sanitation presents significant problems regarding inadequate waste disposal, lack of water treatment and sanitation.